EFEKTIVITAS DAN KINERJA TERHADAP PENGELOLAAN BADAN USAHA MILIK DESA LAGADING KECAMATAN PITU RIASE KABUPATEN SIDENRENG RAPPANG - Gusni Gusni (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2020)
Abstract The purpose of this study is to determine the effect of effectiveness on the management of business entities owned by Lagading District of Pitu Riase, Sidenreng Rappang Regency, To determine the effect of performance on the management of business entities owned by the village of Lagading, District of Pitu Riase, District of Sidenreng Rappang, to determine the effect of effectiveness and performance on the management of business entities owned villages in increasing village original income in Lagading, Pitu Riase District, Sidenreng Rappang Regency. The population in this study is the overall number of households in the lagading village, amounting to 396 consisting of 4 hamlets. The sampling technique used the Slovin formula with the results of 79.8 rounded up to 80 respondents, taken based on the Probability sampling technique, more precisely Random sampling. This type of research is quantitative descriptive. Data collection techniques used in this study were observation, questionnaires, documentation and library research. The collected data is then analyzed using data analysis techniques using a Likert scale, a simple linear regression analysis, then tested with a validity test, a reliability test using SPSS 16.0. Based on the research results of the variables Based on the results of the study of the Effectiveness variable (X1) obtained an average percentage of 57% included in the category of